Telaah Terhadap Pemikiran Al-Ghazali Tentang Pendidikan Islam dalam Kitab Ihya’ Ulumuddin - Saman Hudi (Jurnal Educazione : Jurnal Pendidikan, Pembelajaran dan Bimbingan dan konseling, 2018)
The purpose of this study is to identify Al Ghazali's thoughts on Islamic education in the book Ihya'ulumiddin. The research problem is specifically focused on how Al Ghazali views students, educators, educational materials, methods, and objectives of Islamic education. This is a literature study with a qualitative approach, and the primary data source is the Ihya'Ulumiddin book. This study's analysis employs content analysis and comparisons with other sources. This study discovered that first, students prioritize soul purity and noble character, second, educators prioritize sincerity, sincerity, exemplary, and mastery over student psychology. Third, Educational Materials are very complete and perfect because they cover three aspects: human-God relationships, human-human relationships, and human-nature relationships. Fourth, Al-method Ghazali's is very short and simple, but it requires educator sensitivity when used. Fifth, the goal of Islamic education is to bring one closer to Allah by seeking happiness in this world and the hereafter. Keywords: Al Ghozali’s thought, Islamic education, Ihya’ Ulumuddin